The sequence of the Drosophila melanogaster gene for yolk protein 1. - Hung, M C (1981)
We have determined the complete nucleotide sequence of the hormonally regulated yolk protein 1 (YP1) gene of Drosophila melanogaster. We have also determined the sequence location of the 5' and 3' ends of both the mature mRNA and the gene's only intron. The YP1 gene contains sequences similar to those found in many other eukaryotic genes. Among these sequences are the Hogness-Goldberg box, the capping site, the ribosome binding site and the polyadenylation signal sequence, all perhaps involved in transcriptional or translational control. Also among these sequences are the consensus splice sequences. They occur at each end of the 76 nucleotide intron. One distinctive secondary structure likely to occur in either the DNA or RNA and which might be involved in the regulation of transcription or translation was also found in the YP1 gene sequence. We show the protein sequence predicted by the DNA sequence and the RNA mapping results.